Vitamin E can compensate the density of M1 receptors in the hippocampus of scopolamine-treated rats - Sayyahi, Ali; Jahanshahi, Mehrdad; Amini, Hossein; Sepehri, Hamid (Folia Neuropathologica, 2018)
M1 muscarinic receptor plays a fundamental role in memory and is closely associated with Alzheimer’s disease (AD); it has long been assumed as a therapeutic goal. By activating of the cholinergic receptor vitamin E helps with memory retention. But effects of vitamin E on density of M1 muscarinic receptor-immunoreactive (ir) neurons remain poorly understood. The present research aimed to examine the chronic administration effect of vitamin E against scopolamine-induced memory loss and the number of M1 muscarinic receptor-ir neurons of the hippocampus in male rats. Randomly, 42 adult male Wistar rats were divided to six groups: control, Sham-saline: receiving scopolamine + saline, Sham-sesame oil: receiving scopolamine + sesame oil and three experimental groups: receiving scopolamine + vitamin E with different doses (25, 50, and 100 mg/kg/day, i.p.) for 14 days. The passive avoidance task was used for the memory test. Twenty-four hours after behavioral tests, rats’ brains were taken and fixed, and after tissue processing, sections were stained using the immunohistochemical technique for M1 muscarinic receptor-ir neurons and cresyl violet for neurons. The injection of scopolamine to rats caused memory impairment and vitamin E treatment could ameliorate it. In the scopolamine-treated groups, the number of CA1 and CA3 pyramidal and dentate gyrus (DG) granular neurons was decreased significantly as compared to the control group. Vitamin E treatment significantly increased neuron numbers in the CA1 and CA3 areas of the hippocampus and DG area. Treatment with vitamin E for 14 days could compensate the loss of M1 muscarinic receptor-immunoreactive neuron numbers induced by scopolamine in the hippocampus. The most effective vitamin E dose was 50 mg/kg/day in this study. In conclusion, vitamin E can compensate the neuronal loss in the hippocampal formation and also it can raise the density of M1 receptor-ir muscarinic neurons after an injection of scopolamine.